Tunable band offsets in the BP/P4O10 van der Waals heterostructure: first-principles calculations. Issue 47 (26th November 2018) - Dou, Wenzhen; Huang, Anping; Shi, Hongliang; Zhang, Xinjiang; Zheng, Xiaohu; Wang, Mei; Xiao, Zhisong; Liu, Liming; Chu, Paul K.
Abstract : The separation of photoexcited electron–hole pairs in the BP/P4 O10 vdW heterostructure. Abstract : The structural and electronic properties of the black phosphorus/phosphorus pentoxide (BP/P4 O10 ) van der Waals (vdW) heterostructure are investigated theoretically by first-principles calculations. The BP/P4 O10 vdW heterostructure is a direct bandgap semiconductor with intrinsic type-II band alignment thus facilitating separation of photoexcited charge carriers. A transition from semiconducting to metallic is predicted under a positive electric field and the transition of type-II to type-I band alignment occurs under a negative electric field in the BP/P4 O10 vdW heterostructure. Moreover, the bandgap can be modulated by adjusting the interlayer distance. The results indicate that the band offsets of the BP/P4 O10 vdW heterostructure are tunable, consequently boding well for application to nanoelectronics and optoelectronics.